Latent Constructs of the Static-99R and Static-2002R: A Three-Factor Solution. (February 2016) - Brouillette-Alarie, Sébastien; Babchishin, Kelly M.; Hanson, R. Karl; Helmus, Leslie-Maaike
The most commonly used risk assessment tools for predicting sexual violence focus almost exclusively on static, historical factors (e.g., characteristics of prior offences). Consequently, they are assumed to be unable to directly inform the selection of treatment targets or evaluate change. In this article, we argue that this limitation can be mitigated by using latent variable models as a framework to link historical risk factors to the psychological characteristics of offenders. Accordingly, we conducted a factor analysis of the 13 nonredundant items from the two most commonly used risk tools for sexual offenders (Static-99R and Static-2002R) to identify the psychological information contained in these tools. Three factors were identified: (a) persistence/paraphilia, a construct related to sexual criminality, especially of the pedophilic type; (b) youthful stranger aggression, a construct centered on young age and offence seriousness; and (c) general criminality, a construct that reflected the diversity and magnitude of criminal careers. These constructs predicted sexual recidivism with similar accuracy, but only youthful stranger aggression and general criminality predicted nonsexual recidivism. These results indicate that risk tools for sexual violence are multidimensional, and support a shift from a focus on atheoretical risk markers to the assessment of psychologically meaningful constructs.